(untitled) - AWOTIDE , D. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The study established the relationship among community-based organizations (CBOs) membership, food poverty and welfare status of rural household in Southwest Nigeria. A multistage sampling technique was used to select 240 respondents. The data was analyzed using poverty depth analysis (FGT Class), Logit and ordinary least square regression models. CBOs membership and welfare status were modelled to form indices and incorporated into the regression analyses. Analysis of the poverty measures revealed that most rural dwellers are not poor in theory but are poor in reality. Also, CBO membership, food poverty and welfare status were found to be interwoven, CBO membership significantly determined the poverty level and the welfare status of the rural dwellers. Evidences provided in this study suggest that empowerment of local communities through self-owned and managed community-driven organizations would be a step in the right direction to alleviating poverty and improving the standard of the rural dwellers. Therefore, policies aimed at encouraging the establishment and sustenance of CBOs most especially professional associations, trade associations and cooperative societies should be strongly considered. This is to allow them increase their access to productive capital as well as economies of scale.